Comparative Study on Performance of Beam and Arch Bridge Subjected to Uniformly Distributed Load - Kaafil Rehumaan, Shifana Fatima (International Journal of Architectural Engineering Technology, 2022)
In this paper, an attempt has been made to study the behavior of beam and arch bridges subjected to static uniformly distributed loads. The target audience of this research paper is Architecture students because they would like to visualize the structural concepts for better understanding with minimal calculation. For this reason, a static load test was conducted on three types of beam bridges and on three types of arch bridges. The performance of the arch bridge is studied by changing the type of beam, and the results are compared with the beam bridge. Based on the test results, it is found that the performance of glued beam bridges is recommended for less span than arch bridges.